2015
DOI: 10.1093/geronb/gbv059
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements and Psychological Well-Being of the Older Adults After the Economic Transition in Vietnam

Abstract: Changes in living arrangements induced by differences in labor market opportunities in neighboring regions have resulted in significant differences in psychological well-being among the older adults. The findings point to the need for attention to the mental health of elderly parents left behind in less economically developed regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Similar to our observation about older adult care as family responsibility, Yamada & Teerawichitchainan (2015) conclude that "[i]ntergenerational coresidence significantly increases the psychological well-being of the older adults in Vietnam" while Nguyen & Nguyen (2010) state the following:…”
Section: A Brief Overview Of Gerontology-related Research In Vietnamsupporting
confidence: 77%
“…Similar to our observation about older adult care as family responsibility, Yamada & Teerawichitchainan (2015) conclude that "[i]ntergenerational coresidence significantly increases the psychological well-being of the older adults in Vietnam" while Nguyen & Nguyen (2010) state the following:…”
Section: A Brief Overview Of Gerontology-related Research In Vietnamsupporting
confidence: 77%
“…Marital status and living arrangement are two important objective measures of social isolation and the most commonly reported correlates of loneliness. 6,[50][51][52] We also found non-married status and living alone were significant contributors to loneliness. Traditional Chinese culture highly values family and neighbourhood harmony, which can fulfil needs of OA for social contacts and activities and emotional bonding with others, thereby alleviating loneliness.…”
Section: Discussionmentioning
confidence: 57%
“…Older adults who were left behind by migrant children were more susceptible to psychological distress such as depression [ 75 ]. Intergenerational co-residence has shown to be protective in many countries in different populations including Korea [ 76 ], Japan [ 77 ], China [ 78 , 79 ] and Vietnam [ 80 ]. In Spain, Zunzunegui et al [ 81 ] showed elders living with their children had more instrumental and emotional help and improved physical and mental health.…”
Section: Discussionmentioning
confidence: 99%